Antenatal and Postnatal Care among Women of the Danuwar Community at Panchkhal - Kafle, Bishnumani (Journal of Research and Development, 2022)
Antenatal and postnatal care of mother is so important for the health of mother as well as the baby. Antenatal and postnatal care services are amongst the recommended interventions aimed at preventing maternal and newborn deaths worldwide. The objective of this research study was to assess the antenatal and postnatal care and practice of the Danuwar community at Panchkhal. This study was conducted in Panchkhal ward no 8, Pipaltar, Kavre. A descriptive study design was used for the study. There were total 198households in Pipaltar ward no eight. 50 percent households (99 households) were taken through simple random sampling procedure. The respondents were married Danuwar women aged from 15-49 either pregnant or having children. Only one respondent was taken from each sample household. Interview schedule were used to collect the data. The finding of the study revealed that majority of the respondents (66.67%) women had health checked up during pregnancy. Rest of them had not checked up health because of lack of knowledge, shyness and lack of time. Most of the pregnant women faced vomiting, abdominal pain, weakness, bleeding, backache, tiredness health complication during the period of pregnancy. Most of the pregnant women (68.69%) had taken T.T. injection and normal diet during pregnancy. Almost (92.93%) women were kept at unsafe places after delivery because of the custom and most of the Danuwar women (97.98%) had no practice of going to health center for health check-up after delivery. Almost all of the Danuwar women consumed ‘Juwano’ soup, meat, ghee in the period of postnatal (within 6 weeks after delivery).